POLA KOMUNIKASI ANTARA PELATIH DAN ATLET PENCAK SILAT DALAM MENINGKATKAN MOTIVASI KOMPETISI TINGKAT DAERAH (Studi Kasus PSHT Rayon Mojosongo Cabang Kota Surakarta ) - Wisnu Wardhana, Paksi Pramudya; Sekar Wangi, Maya; Muadz, Muadz (Solidaritas, 2024)
Pencak silat is one of the riches of martial arts in Indonesia. The latest Indonesianpencak silat has made many achievements both at the national and regional andASEAN levels. This achievement sparked the motivation of athletes to continue to compete and develop. As what is done by the coach of PSHT Rayon Mojosongo in orderto increase the motivation to compete for his foster children, the coach continues to workhard, practice and also strengthen his chemistry and interpersonal communication. Thepurpose of this study is to analyse and describe the application of interpersonalcommunication of coaches to PSHT athletes in order to increase motivation toparticipate in regional level competitions. This type of research uses a case studyapproach method of leadership leadership of pencak silat hati teratai Rayon Mojosongo.The data collection method was conducted through interviews with informants. Theinformants selected consisted of coaches, athletes who had participated in regional scalecompetitions and 1 member of PSHT Rayon Mojosongo.The results showed that the coach in applying interpersonal communication toathletes of PSHT Rayon Mojosongo Surakarta City Branch used standard indicatorsincluding openness, empathy, mutual support, positive attitude and the existence ofcommon goals or interests. The application of communication is successful and canincrease the motivation of athletes to participate in competitions at the regional level. Inaddition, the application of interpersonal communication is also carried out bycombining the wheel type communication style.Keywords: Communication Patterns, Interpersonal Communication and CompetitionMotivation